Mythologeme-Related Crisis of Identity: Reality and Fictional Markers of Alienation - Svitlana Balinchenko (International Society of Philosophy and Cosmology, 2019)
The paper observes some myth-triggered communicative distortions caused by mass-media distribution of common stereotypes of the Other. Another focal point of the article is the variety of possible mechanisms for overcoming the myths which emerged in the Ukrainian context of the hybrid war. The transformation from reality to counter-reality has been considered in terms of norm-oriented actions of an individual (with the focus of sameness and wholeness of self-concept connected to reality). The latter is opposed to the projected and split identity of the "dividuum" or Subiectum Neglegens textually involved in creating practical concepts and ignoring or eliminating counter-real mythologemes of Russian World and Split while being engaged in civic and political discourses. Thus, constructive and destructive ignoring has been evaluated according to the effect on the communicative actors: ignoring differences is compared with ignoring on the basis of differences in the social reality-forming legal texts. The normative changes resulted from the introduction of the practical concepts into the legislative field are observed from the perspective of the problem of internally displaced persons (IDPs) in Ukraine. This group of Ukrainians has been overcoming physical, legal and mental transposition from We-group to Other- or even Alien-group, and in some cases - to We-group again, as a result of an internal conflict of myth-based processes during the crisis identity shift.